Enraged North, Omitted South: Early Twentieth Century Chinese Islamophobic Discourses, Varying Muslim Reactions, and Global Media Capitalism - Chan, Tsz Kit (The 29th International Congress of DAVO in Cooperation with the „Turkologentag 2023 – Fourth European Convention on Turkic, Ottoman and Turkish Studies“, 2023)
As a vital medium of nineteenth-century Chinese exclusivist national discourses, print periodicals were developed with massive support from the Chinese diaspora in majority-Muslim Southeast Asia. To satisfy readers’ curiosity and promote national geopolitical agendas in the 1920s-30s, Chinese periodicals covered cultural others like Muslims through rigid national categories and orientalist gaze engendered by imitating Western media capitalism and knowledge regime. These global enmeshments repeatedly circulated pejorative discourses about Muslims within and outside China, with a master narrative of Muslims being ‘descendants of pigs’. As a result, Chinese Muslims reacted with various strategies while mediatizing their responses in their periodicals. However, the intensity of Muslim reactions differed towards pejoratives addressing their coreligionists within or outside China’s border. This article focuses on two Chinese media Islamophobic incidents in 1931-1932 regarding Muslims in Southeast Asia and Northwestern China. The different receptions demonstrate the asymmetry within national discursive practices regarding Islamophobic discourses materialized by global connectedness. By taking periodical studies’ perspective and corpus-assisted discourse analysis, this article considers the agencies of Muslim and non-Muslim Chinese periodicals in circulating and steering (counter)discriminative discourses and actions of historical actors. Not only did periodicals serve as a medium containing some narratives about Muslims, but the material dimensions of periodicals – like publishing institutions and print products – provided tools and objects for historical agents to redirect their affects. Hence, Muslims could channel their grievances physically upon the publishers and negotiate how Islam should be talked about in the Chinese public sphere, eventually drawing the Chinese state into the negotiation.<br
Keywords: Chinese Muslim; Islamophobic Discourses; Corpus Analysis

How Foreign Enterprises Challenged Chinese Regional Finance: A Case Study of the Operation of Asiatic Petroleum and Standard Oil in Suzhou in the 1910s - Chan, Tsz Kit (Dynamics and Experiences of Globalization – Global Crises, Deviance, and Threats, 2022)
As the Treaty of Tientsin concluded in 1858 as an outcome of the Qing Empire’s defeat in the Second Opium War, a treaty port system was established, allowing British subjects to carry out commercial activities in the name of “free trade.” However, since the Qing and British delegates were communicating and operating on distinctive political and economic frameworks, the foundation of this treaty port system left out plenty of zones of ambiguity, which state actors and merchants on both sides constantly maneuvered in the coming decades. As a result, when incidents of commercial disputes unfolded, they were not merely about money but also power, statecraft, and principles. Against this background, this research selects and focuses on the commercial disputes between foreign enterprises, native compradors, and domestic merchants in Suzhou in the 1910s, one of the wealthiest regions in China that produced most of the empire’s commercial levies. Specifically, it looks at how two foreign enterprises, namely Asiatic Petroleum (the former body of Royal Dutch Shell) and Standard Oil, challenged the public finance of the regional government on their pathway to maximize profits in the framework of treaty stipulations. Interestingly, because of the nuanced relationship between central and regional finance, even ordinary business operations (i.e., avoiding duplicated levies and setting up warehouses) could already cause unintended consequences that exerted fiscal pressure on local governments. Collective actions like protests for tax discretion and tax strikes became more frequent. Meanwhile, news about these incidents got disseminated by the burgeoning Chinese newspapers, which increasingly took the vantage point of native merchants and national interests. A new political and economic discourse started articulating due to the existence of foreign enterprises in China. In a brushstroke, this research points to some inevitable problems local governments and native merchants encountered in economic globalization. Furthermore, with the spotlight tilted towards the emerging Chinese Chambers of Commerce at the time, this research also provides a descriptive account of how merchants developed a primordial sense of solidarity and self-consciousness out of the challenges posed by globalization. In this sense, it hopes to resonate the 20th International Summer School of the Graduate School Global and Area Studies in 20

The Changing Narratives on Lijin from Late Qing to the Republican Era (1875-1931) - Chan, Tsz Kit (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
What is a tax? Who collects it for what purpose? How is it justified? Across cultures and times, people hold different answers to these questions in their respective languages and devices of reasoning. This research probes the knowledge production process of these answers in Chinese history and provides a descriptive and analytical account of the controversy of a transit duty called lijin from 1853 to 1931, a period of turbulence in which China was entangled with challenges of globalization, internal strife, and social and cultural modernization. Apart from all the variables from the late nineteenth century to the early twentieth century, what was apparent was that the Chinese fiscal structure experienced a radical transition. Specifically, taxation depending on commercial activities became dominant in state revenue, rising from 10% in 1841 to over 60% in 1890. In this transition, the establishment of lijin amidst the Taiping Rebellion in the mid-1850s was an especially crucial episode. In hindsight, lijin not only rescued the empire from its prolonged civil warfare but also de-railed the political equilibrium between the throne, provincial governors, and rural gentry. In other words, the green light to fiscal autonomy granted on local levels compromised the power balance that had formed the backbone of China’s dynastic structure. Many have studied the monetary aspect of the above history, but very few focus on the new discursive fabrics that followed China’s unprecedented changes in public finance. This research examines the semantic changes happening in China’s capitalistic transformation and traces these changes to the social and political factors that produced them. In order to narrow down the scope, this research uses the media materials about lijin to identify the new discourses that reshaped the idea of public finance in China’s encounter with the global expansion of capitalism. Over the years, historians’ interest in lijin was mainly to uncover archival evidence and overcome the statistical challenges of its incomplete records. Instead, this research looks at the language choices, the argumentative tools and frameworks, and the social discourses that embedded the lijin debates. With a Corpus-assisted Critical Discourse Analysis, this dissertation uses Chinese experiences to shed light on how the ideology of public finance interacted with the project of modern state-building and how the identity of individuals and social groups gradually reconfigured alongside their relations with each other.<br
Keywords: Chinese History; Fiscal History: Tariff Policy: Media Studies